Nurse provision of healthy lifestyle advice to people who are overweight or obese. (22nd July 2015) - Kable, Ashley; James, Carole; Snodgrass, Suzanne; Plotnikoff, Ronald; Guest, Maya; Ashby, Samantha; Oldmeadow, Christopher; Collins, Clare
Abstract A cross‐sectional survey was conducted in a regional area in Australia to measure nurses' perceptions, practices, and knowledge in regard to providing healthy lifestyle advice to people who are overweight or obese. Responses were compared between geographic regions. Participation was voluntary and anonymous. Of the 79 nurse participants, 68% considered that provision of healthy lifestyle advice was within their scope of practice. Only 28% reported frequently estimating body mass index in the practice setting. Nurses often recommended increasing activity levels (44%), but recommended reducing daily caloric intake less often (25%). Nurses' knowledge about weight management was variable and the proportion of correct answers to knowledge items ranged from 33–99%. Nurses have many opportunities to deliver healthy lifestyle advice in a range of practice settings. The variation in practices and knowledge of nurses indicates a need for improved healthy lifestyle education for undergraduate and practicing nurses.